2019
DOI: 10.1007/s12630-019-01349-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative glucose variability, but not average glucose concentration, may be a risk factor for acute kidney injury after cardiac surgery: a retrospective study

Abstract: Intraoperative glucose variability, but not average glucose concentration, may be a risk factor for acute kidney injury after cardiac surgery: a retrospective study La variabilité glycémique peropératoire, et non la concentration glycémique moyenne, pourrait être un facteur de risque d'insuffisance rénale aiguë après une chirurgie cardiaque: une étude rétrospective Abstract Purpose Altered perioperative glycemic control may contribute to the development of renal dysfunction in cardiac surgery patients. Neverth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The accuracy of HbA1c is affected by the patient's anemia, hemoglobin variants, and so on [Ang 2015;Nitin 2010;Weykamp 2013]. Recently, some studies reported that other indicators, such as TIR, GV, GA, TyG, and others show good predictive value for renal complications [Yoo 2017;Saik 2020;Ding 2013;Clement 2019;Nam 2019;Varghese 2021;Qin 2020]. The preoperative HbA1c level only represents the patient's preoperative blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of HbA1c is affected by the patient's anemia, hemoglobin variants, and so on [Ang 2015;Nitin 2010;Weykamp 2013]. Recently, some studies reported that other indicators, such as TIR, GV, GA, TyG, and others show good predictive value for renal complications [Yoo 2017;Saik 2020;Ding 2013;Clement 2019;Nam 2019;Varghese 2021;Qin 2020]. The preoperative HbA1c level only represents the patient's preoperative blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…59 Nam et al found intraoperative glucose variability, but not the average glucose concentration itself, as a risk factor for acute kidney injury (AKI) after cardiac surgery. 60 The impact of admission hyperglycemia on development of AKI in patients with AMI was found by Moriyama et al 61 Hence, a fair amount of literature exists, discussing the significance of glycemic management in cardiac critically ill patients and the complications arising out of episodes of DG. However, when it comes to nutrition intervention for managing DG, the literature is scarce.…”
Section: Cardiac Patientsmentioning
confidence: 98%
“…Furthermore, intraoperative GV may negatively influence the outcomes after cardiac surgery. Indeed, recent evidence recognized GV as an independent risk factor for early postoperative acute kidney injury [43]. In addition, for patients who underwent scheduled coronary artery bypass grafting (CABG) surgery, post-operative GV was associated with poor short-term outcomes, including increased risk of post-operative atrial fibrillation (AF), cardiac arrest, pneumonia, renal failure, stroke, sepsis, reoperation, and mortality [13,[44][45][46].…”
Section: Glycemic Variability and Stable Coronary Artery Diseasementioning
confidence: 99%